Late-onset seizures and epilepsy: Electroclinical features suggestive of autoimmune etiology - Morano, Alessandra; Cerulli Irelli, Emanuele; Salamone, Enrico Michele; Orlando, Biagio; Fanella, Martina; Tinelli, Emanuele; Ruffolo, Gabriele; Zuliani, Luigi; Fattouch, Jinane; Manfredi, Mario; Giallonardo, Anna Teresa; Di Bonaventura, Carlo (Frontiers in Neurology, 2022)
Introduction. Late-onset epilepsy (LOE) has recently become a topic of intense research. Beside stroke, tumors and dementia, autoimmune encephalitis (AE) has emerged as another possible cause of recurrent seizures in the elderly, and may account for a proportion of cases of unknown origin (LOEUO). This 24-h ambulatory EEG (AEEG)-based study compared LOEUO and AE patients to identify features suggestive of immune-mediated seizures in the elderly. Materials and Methods. We retrospectively reviewed 232 AEEG exams performed in patients over 55 years with ≥ 6-month follow-up, and selected 21 subjects with AE and 25 with LOEUO. Clinical charts and AEEG recordings were carefully analyzed. Results. Twenty-five LOEUO patients (12 women, mean age at onset 67.9 years) and 21 AE subjects (8 women, mean age 65.7 years) were enrolled. High-frequency seizures were reported in 20/21 AE and 7/25 LOEUO cases (p<0.00001). Focal aware seizures were more common in AE (14/21 vs 6/25, p=0.00058), whereas ‘isolated’ focal-to-bilateral tonic-clonic seizures occurred in 5/25 LOEUO patients only (p=0.053). AE subjects reported ictal autonomic manifestations more frequently (p=0.0033). Three-hundred-seventy and 24 seizures were recorded in 13/21 AE and 3/25 LOEUO patients, respectively (p=0.0006). Interictal epileptiform discharges were observed in 70% of both groups, but their sleep activation was more common in AE (p=0.06). Conclusion. Our study shows that high frequency focal seizures with autonomic manifestations should raise the suspicion of AE in elderly with new-onset seizures. It also highlights the relevant contribution of AEEG, which might reduce the diagnostic delay and provide useful clues to recognize AE.